Ferulic Acid: Signaling Pathways in Aging - Neopane, Deepa; Ansari, Vaseem Ahamad; Singh, Aditya (Drug Research, 2023)
The need for clinical remedies to the multiple age-related deficiencies in skin function brought on by extrinsic and intrinsic causes is increased by these demographic changes. Reactive oxygen species (ROS), mitochondrial deoxyribonucleic acid (mtDNA) mutations, telomere shortening, as well as other factors, contribute to the aging of the skin. In this overview, the issue of human skin aging is introduced, along with several pathways and the protective effects of ferulic acid in light of current patents. The complex antioxidant effect of ferulic acid depends on the “sweeping” away of free radicals as well as the suppression of the synthesis of ROS or nitrogen. Furthermore, Cu (II) or Fe protonated metal ions are chelated by this acid (II). Ferulic acid is a free radical scavenger as well as an enzyme inhibitor, increasing the activity of enzymes that scavenge free radicals while decreasing the activity of enzymes that speed up the creation of free radicals. AMPK signalling, which can regulate cellular homeostasis, stress tolerance, cell survival and proliferation, cell death, and autophagy, has recently been linked to aging and lifespan. Therefore, Caenorhabditis elegans (C. elegans) and rodents had longer life-spans due to specific AMPK activation. By inhibiting the TGF-β/Smad signalling pathway, UV irradiation can reduce the production of procollagen. Glycation changes the skin’s physical characteristics, making it less elastic and stiffer. . Excessive free radicals simultaneously trigger the nuclear factor kappa B (NF- κB) signalling pathway, increasing TNF levels and matrix metalloproteinase production (MMPs).
Keywords: AMPK signalling; NF-κB signaling; aging; reactive oxygen species; ferulic acid